Aspects Concerning the European Civil Code - Bularca Anca Roxana (The 6th International Conference Challenges in Higher Education and Research in the 21st Century, Heron Press, 2008)
The article reports one of the many interesting research projects being undertaken in Europe with a viewtothe possible unification or harmonisation of some aspects of private law. The Europeanization of Private Lawis an important challenge that concems the member states of the European Union. The paper analyses the opportunity of the European Civil Code and the effects that could emerge due to these new regulations. The principles that mIe the domain of contracts and the limits of regulation represent a major task that has ta be discussed during the process of Europeanization of Private Law